Youth pathways in dairy in Kenya - International Livestock Research Institute (International Livestock Research Institute, 2020)
This video highlights views from youth who are engaged in dairy farming as part of research by ILRI to understand current and emerging ways that youth participate in the dairy subsector in East Africa.